Compostagem de resíduos agroindustriais : uma abordagem utilizando o projeto experimental de misturas - Gaspodini, Raquel Sotille (2015)
Composting is a biological process able to treat and recycle solid waste, turning them into fertilizers, bringing both environmental benefits and economic recovery of the organic compound formed. In this context, this research focused on the acquisition of knowledge and the evaluation of the potential of mixtures made from three different agro-industrial wastes (eggshell, manure and sludge of wastewater treatment of rendering plant) to be treated by means of a composting process. Usually, the most frequent use of these wastes is the disposal in agricultural soil, which has proven inadequate especially in times of heavy rainfall or continuous planting periods. Fourteen small-scale reactors, aerated by manual revolving were used, each of them fed with 105 kg of variable mixtures of the three industrial residues, defined through a simplex-centroid experimental design. The composting process was monitored by measuring the evolution with time of temperature, humidity, pH, and C/N ratio. In addition, at the end of the process the following parameters were analyzed: organic carbon, nitrogen, total phosphorus, potassium, calcium, magnesium, salmonella sp. and thermotolerant coliforms. The thermophilic phase lasted approximately 38 days. After 46 days, the mass under degradation reached the ambient temperature, being then allowed to mature for another 32 days. The best results were obtained for ternary mixtures with equal component proportions (33,3% of eggshell, 33,3% of manure, and 33.3% of sludge), a unit for mixing with 100 % eggshell and for the mixture containing 16,7% of eggshell, 16,7% of manure, and 66,7% of sludge, which amongst the parameters established by the Normative Instruction 25/2009 of the Brazilian Ministry of Agriculture, Livestock, and Food Supply, only the magnesium did not fit the required range. Also, most mixtures did not reach temperatures that promote the elimination of coliforms thermotolerant, but all showed no salmonella sp. At the end, results have shown that even though this process was carried out on a small scale, it was possible to compost these materials and generate a good quality compost for later use in agriculture